Apherdianus, 16th-century Dutch proverbs and the Woordenboek der Nederlandsche Taal (WNT) - Mooijaart, M (2010)
In the year 1552 Petrus Apherdianus published his Tyrocinium linguæ Latinæ, a textbook for students to practice Latin. The Dutch translations of the Latin examples in this book contain a number of idomatic expressions. In the same year 1552 the Amsterdam copyist Reyer Gheurtz wrote his collection of Dutch proverbs, _Adagia. His manuscript is only one of the large number of 16th-century proverb collections compiled in the Low Countries. This paper sketches the relationship between the Dutch proverbs and other idoms in Apherdianus' schoolbook and the content of several 16th-century proverb collections, and investigates their treatment in the Woordenboek der Nederlandsche Taal (Dictionary of the Dutch Language - WNT). The aim is to gain insight in the position of proverbs in everyday usage in older Dutch.